AMPK mediates a pro‐survival autophagy downstream of PARP‐1 activation in response to DNA alkylating agents. Issue 2 (29th November 2012) - Zhou, Jing; Ng, Shukie; Huang, Qing; Wu, You-Tong; Li, Zhengqiu; Yao, Shao Q.; Shen, Han-Ming
Abstract : In this study we aim to elucidate the signaling pathway and biological function of autophagy induced by MNNG, a commonly used DNA alkylating agent. We first observed that MNNG is able to induce necrotic cell death and autophagy in Bax−/− Bak−/− double knockout MEFs. We analyzed the critical role of PARP‐1 activation and ATP depletion in MNNG‐mediated cell death and autophagy via AMPK activation and mTOR suppression. We provide evidence that suppression of AMPK blocks MNNG‐induced autophagy and enhances cell death, suggesting the pro‐survival function of autophagy in MNNG‐treated cells. Taken together, data from this study reveal a novel mechanism in controlling MNNG‐mediated autophagy via AMPK activation downstream of PARP‐1 activation and ATP depletion. Abstract : ► MNNG induces necrotic cell death and autophagy in Bax−/− Bak−/− DKO MEFs, via PARP‐1 activation and ATP depletion. ► PARP‐1 activation and ATP depletion lead to AMPK activation, mTOR suppression and induction of autophagy. ► Autophagy plays a pro‐survival function in MNNG‐mediated necrotic cell death.